Monitoring training response with heart rate variability in elite adolescent athletes: is there a difference between judoka and swimmers? - Mourot, L.; Vacher, P.; Nicolas, M. (Archives of Budo, 2016)
Background and Study Aim: Previous studies in adults and endurance athletes have evaluated whether heart rate variability (HRV) can be used to monitor training load. We aimed to answer to question: whether HRV monitoring is useful in elite adolescent athletes practicing a sport with a major anaerobic component, i.e. judo.